Asymptomatic Crohn’s disease presenting as perianal masses in a child: A case report and literature review - Samia Rahman; Loretta Fiorillo (SAGE Open Medical Case Reports)
A 7-year-old male presented to our outpatient pediatric dermatology clinic for enlarging perianal masses initially suspected to be warts. Family endorsed a 2-year history of generally poor growth but denied gastrointestinal symptoms at our initial visit. Physical examination revealed three fleshy, pedunculated, violaceous masses around the anal sphincter that were rubbery in texture. Pathology indicated inflammatory polyps and further investigations confirmed the diagnosis of anal skin tags secondary to highly active and severe Crohn’s disease. This case highlights the essential role of dermatologists in recognizing perianal masses as potential indicators of Crohn’s disease, even when classic gastrointestinal symptoms are initially absent, as these findings can enable timely diagnosis and management.